2019
DOI: 10.1177/0885328219873174
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vivo evaluation of surface heparinized small diameter tissue engineered vascular scaffolds of poly(ε-caprolactone) embedded with collagen suture

Abstract: Herein biodegradable poly(e-caprolactone) was electrospun into tubular microfibrous scaffolds and modified by the surface heparinization and wrapping of Type I collagen suture for enhancing anticoagulation activity and mechanical properties. The resulting scaffolds were featured by a double distribution of microfiber diameters ranged in 2.74 AE 0.44 and 5.15 AE 0.63 mm on the outer surface with tensile strength of 1.36 AE 0.37 MPa and Young's modulus of 8.31 AE 1.87 MPa. The burst pressure after embedded with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…Heparin functionalization of synthetic small‐diameter TEVGs is an often‐reported strategy to prevent thrombus formation. [ 45–54 ] Surprisingly, we did not observe a clear reduction in platelet activation in the hep group when compared to bare group (Figure S3, Supporting Information). This observation, in case of heparin functionalized groups (either with or without IL‐4), is in apparent contrast with the canonical definition of heparin as a potent anticoagulant.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Heparin functionalization of synthetic small‐diameter TEVGs is an often‐reported strategy to prevent thrombus formation. [ 45–54 ] Surprisingly, we did not observe a clear reduction in platelet activation in the hep group when compared to bare group (Figure S3, Supporting Information). This observation, in case of heparin functionalized groups (either with or without IL‐4), is in apparent contrast with the canonical definition of heparin as a potent anticoagulant.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies showed a positive effect of heparin functionalization of small‐diameter TEVGs on patency and tissue regeneration. [ 45–49,58,59 ] A recent example is a study by Matsuzaki et al., in which higher patency rates (85%) were reported for heparin‐eluting bilayered polycaprolactone/poly( l ‐lactide‐ co ‐caprolactone) (PCL‐PLCL) vascular grafts compared to non‐heparin grafts (20%) in carotid artery interposition replacement during 8 weeks follow‐up in sheep. [ 50 ] In contrast, other studies report adverse events with the heparin functionalization of small‐diameter TEVGs, with local formation of an α SMA‐rich neointimal layer in heparin functionalized grafts.…”
Section: Discussionmentioning
confidence: 99%
“…PCLH scaffold preparation was performed according to our previously published literature. ,, In short, PCL was dissolved in a DCM/methanol (volume ratio: 5:1) solution at a concentration of 0.2 g/mL. The electrospinning parameters were set as follows: a voltage of 15 kV, receive distance of 17 cm, and injection rate of 3 mL/h to obtain a tubular PCL scaffold.…”
Section: Methodsmentioning
confidence: 99%
“…The structure and function of regenerated blood vessel were similar to those of the native aorta after three months, showing the promising potential of in situ VTE. We also prepared small-diameter heparin-modified PCL (PCLH) scaffolds by electrospinning and directly implanting them into animal models including rats, rabbits, and canines according to the concept of in situ VTE. The PCLH scaffold can maintain long-term in vivo patency . However, a high aneurysm incidence was observed in all animal models (4/10 in rats, 1/1 in canines, and 4/6 in rabbits), which negatively impacts the success of VTE grafts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation